Long‐term effects of chemotherapy and radiation received during early childhood on the developing dentition of pediatric cancer patients. (23rd May 2022) - Rahul, Morankar; Atif, Mohammad; Ganguly, Shuvadeep; Pushpam, Deepam; Tewari, Nitesh; Mathur, Vijay; Bakhshi, Sameer
Abstract: Introduction: The short‐term effects of chemotherapy and irradiation are well documented; however, there is paucity regarding their long‐term effects, especially in children and adolescents. Case Description: This paper discusses the long‐term effects of chemotherapy and/or radiation received by the patients during their early childhood on the developing dentition. It comprises the compilation of 11 cases with alteration in the dental development screened from 138 cases of the childhood cancer patients who received the chemotherapy and/or radiation as a part of anticancer therapy. Results and Conclusion: The findings revealed that the age of initiation of anticancer therapy along with the synergistic effect of chemo‐irradiation, and the dose of radiation used were the principal determinants for the dental abnormalities. The root‐related abnormalities were found to be varied and more common as compared to the missing teeth and defects related to the tooth crown.